2009
DOI: 10.1097/qai.0b013e3181af83d6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cognition During Antiretroviral Therapy: Comparison of 2 Different Ranking Systems to Measure Antiretroviral Drug Efficacy on HIV-Associated Neurocognitive Disorders

Abstract: The CPE score represents a step forward toward the identification of a clinically useful approach to estimating HAART ability to improve cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
84
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 19 publications
2
84
1
1
Order By: Relevance
“…Tozzi et al [18] and Letendre et al [21] both found an association between higher CPE regimens and improved neuropsychological function. This finding was expected, given the improved CSF VL control.…”
Section: Follow-up Assessments N=121mentioning
confidence: 97%
See 3 more Smart Citations
“…Tozzi et al [18] and Letendre et al [21] both found an association between higher CPE regimens and improved neuropsychological function. This finding was expected, given the improved CSF VL control.…”
Section: Follow-up Assessments N=121mentioning
confidence: 97%
“…Letendre et al [21] also noted that neuropsychological improvement was greater in ART-naïve participants, possibly because participants on ART accumulated resistant mutations. Some of the above studies have been done using ART-naïve participants, [18,19] and others naïve and experienced participants. [20][21][22] Not all studies measured both CSF VL response and cognitive outcomes.…”
Section: Follow-up Assessments N=121mentioning
confidence: 99%
See 2 more Smart Citations
“…Letendre et al have reported that the CPE score was correlated with CSF viral load [23] and an updated guideline of CPE scoring was recently published [24]. Other studies have reported a correlation of high CPE score with better neurocognitive performance [25,26] while one study demonstrated worsened neurocognitive performance in HIV-infected individuals receiving ARV regimens with high CPE scores [27]. In addition, the intensification of CNS penetration by changing ARV regimens did not further decrease CSF viral load [28].…”
Section: Pornpun Vivithanapornmentioning
confidence: 99%